Selected aspects of diversity of synanthropic flora in the chosen cities of central Poland - Bomanowska, Anna; Witosławski, Piotr (Biodiversity: Research and Conservation, 2008)
Changes in the geographical-historical, biological and ecological structure of synanthropic flora are among visible effects of urban development pressure. Taxonomic and geographical-historical diversity of synanthropic floras was analysed for the selected cities in central Poland: Łódź, Piotrków Trybunalski, Tomaszów Mazowiecki, Zgierz, Pabianice, Bełchatów and Radomsko. Floras of the analysed cities encompass 954 vascular plant species and are characterised by conspicuous uniformity (30.5% of species occur in all investigated cities). The most uniform flora is that of archaeophytes, followed by apophytes, kenophytes and diaphytes. The city of major importance for the spatial floristic system of cities in central Poland is Łódź. The flora of Łódź is characterised by highest species richness (820 species) and specificity (11.7% of the total pool of species and as many as 38.8% of diaphytes occur exclusively in Łódź), highest share of kenophytes (19.6%) as well as anthropophytes (56.3%), and the lowest share of archaeophytes (13.9%). Similarity analysis and classification conducted for total floras and separately for geographical-historical groups of plants in individual cities led on both occasions to the separation of two distinct groups of objects, the first consisting of the territorially adjacent Łódź, Zgierz and Pabianice (excluding the classification based on archaeophytes) and the second consisting of remaining cities.